Structural behaviour of beam with HDPE plastic balls subjected to flexure load - Mohamad, Noridah; Goh, Wan Inn; Samad, A.A.A.; Lockman, A.; Hadipramana, Josef (Trans Tech Publications Ltd, 2017)
This paper presents the structural behavior of reinforced concrete beam embedded with high density polyethylene balls (HDPE) subjected to flexural load. The HDPE balls with 180 mm diameter were embedded to create the spherical voids in the beam which lead to reduction in its self-weight. Two beam specimens with HDPE balls (RC-HDPE) and one solid beam (RC-S) with dimension 250 mm x 300 mm x 1100 mm were cast and tested until failure. The results are analysed in the context of its ultimate load, load-deflection profile, and crack pattern and failure mode. It was found that the ultimate load of RC-HDPE was reduced by 32% compared to RC-S beam while the maximum deflection at its mid span was increased by 4%. However, RC-HDPE is noticed to be more ductile compared to RC-S beam. Both types of beams experienced flexure cracks and diagonal tension cracks before failure